Effect of melatonin on the production of silk - G.SIRISHA,; N.ANITHA, (International Journal of Pharma and Bio Sciences, 2017)
The silkworm (Bombyx mori L) hybrid (PM X NB4D2) were sprayed with different concentrations of melatonin (i.e.10-9, 10-10, 10-11 g/g) on alternate days from the beginning of IV instar to the end of V instar. Melatonin treatment at the concentration of 10-9 g/g showed significant increase in the levels of fibronin in the cocoon and quality of silk when compared to control. Further melatonin treatment at the concentration of 10-9 g/g significantly increased size, weight of silk gland, net weight of the cocoon and ultimately resulted in production of finer quality of silk. From the present data, it can be suggested that topical application of 10-9g/g melatonin resulted in increased quality and quantity of silk from the silkworm.